Sacred Heritage Monastic Archaeology, Identities, Beliefs - Gilchrist, Roberta (Humanities, 2019)
Critically evaluates the concept of sacred heritage, drawing on multi-disciplinary, global perspectives to clarify the multiple values of sacred heritage to spiritual and humanist audiences. Forges innovative connections between medieval archaeology and heritage studies, revealing new perspectives on medieval monasticism, identity, and healing. This title is also available as Open Access.